Productive performance of dairy cows fed millet or corn silage - Do Rêgo, Aníbal C.; Siqueira, Gustavo R. [UNESP]; de Oliveira, Mauro D. S. [UNESP]; Almeida, Geraldo B. de S.; Cardoso, Marcus V. S. B.; de Resende, Flávio D. [UNESP]; Signoretti, Ricardo D. (FapUNIFESP (SciELO), 2025)
The objective of this study was to determine the effect of particle size and inoculation in millet silage compared to corn silage in diets of crossbred 3/4 Holstein × 1/4 Gir cows on diet intake and digestibility, as well as milk production and composition. Five cows were used, with 100 ± 26 d in lactation and a mean body weight (BW) of 509 ± 53 kg, in a 5 × 5 Latin square experimental design. Millet silage with 5 or 20 mm particle size, inoculated or not with Propionibacterium acidipropionici and Lactiplantibacillus plantarum, was evaluated in the diets, and compared with corn silage. Cows fed with corn silage showed a higher intake of dry matter (DM), organic matter (OM), total carbohydrates (TC), and neutral detergent fiber (NDF) than cows fed diets containing millet silage. The DM digestibility of the corn silage diet was higher than that of the diets containing millet silage. Cows fed a diet containing corn silage produced more milk than cows fed diets containing millet silage. Cows fed diets containing millet silage with 20 mm particle size compared to 5 mm showed better productive efficiency, 1.05 and 0.94 kg of milk/kg of DM intake, respectively. Cows fed diets containing corn silage produced more milk than cows fed diets containing millet silage.
Desempenho de vacas leiteiras alimentadas com silagem de milheto ou de milho
Keywords: Ensiling; Lactiplantibacillus plantarum; Particle size; Pennisetum glaucum; Propionibacterium acidipropionici